Synthesis of Some New 1-Carboxamido-3-(substituted-2-hydroxy phenyl)-5-aryl-Δ2-pyrazolines - Utale, P.S.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
2'-Hydroxychalcone an aqueous solution of semicarbazidehydrochloride were refluxed in ethanol for 3 h. The reaction mixturewas cooled, filtered and crystallised from ethanol-acetic acid mixtureto get 1-carboxamido-3-(substituted-2-hydroxyphenyl)-5-aryldΔ2 -pyrazoline. All these synthesised new pyrazolines were testedagainst organism. The Minimum Inhibitory Concentration (MIC)values were determind by using serial dilution method.